STUDY OF PHARMACOLOGICAL ACTIVITY IN SUBLIMATED CULTURE LIQUID OF ALLOGENIC, XENOGENEIC HEPATOCYTES AND FIBROBLASTS FOR THE CORRECTION OF LIVER DAMAGES IN CARBON TETRACHLORIDE INTOXICATION - Marina Razumova; Ekaterina Litvinova; Vassili Gavriliouk (Belgorod National Research University, 2017)
Introduction: At the present time many clinical and experimental studies are devoted to the correction of hepatocytes and liver functional abnormalities with the use of cellular technologies. Materials and methods: Experimental studies were performed on 175 Wistar rats weighing from 120 to 140 g. Acute toxic liver damages (ATLD) in laboratory animals was simulated by intramuscular injection of carbon tetrachloride (CTC) at a dose of 3 ml/kg as 50% solution in olive oil five times with an interval of 24 h. Results and discussion: The introduction of Essentiale H and hypoxen to the animals with ATLD enabled to normalize PTI, TAA and the activity of antioxidant defense enzymes (SOD and catalase) and corrected the concentrations of MDA and SMON. Simultaneous introduction of CLAH proteins, Essentiale H and hypoxen to animals with acute toxic liver damage, in comparison with the previous groups of experimental animals, additionally normalizes the concentration of MDA and SMON in blood plasma. Combined administration of Essentiale N, hypoxen and CLAH proteins, in comparison with the previous groups of experimental animals, normalizes the concentration of MDA, SOD activity, sorption capacity of erythrocytes. Conclusion: The administration of hepatocytes culture liquid of intact rats in combination with pharmacological preparations (Essentiale Forte H and Hypoxen) to allogeneic recipients intoxicated with CTC corrects systemic metabolic disorders arising from the action of hepatotrophic poison more efficiently, in comparison with their separate use.